Induksi Perakaran Anggrek (Dendrobium sp.) Secara In Vitro dengan Penambahan Indole Butyric Acid (IBA) dan Bubur Pisang Raja (Musa paradisiaca L) - Harahap, Fauziyah; Sudibyo, Mufti; Sari, Elvira Nanda; Suriani, Cicik; Edi, Syahmi; Panggabean, Nurul Huda; Daulay, Abdul Hakim (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to obtain a good concentration of IBA and plantain and is suitable for root induction in Dendrobium sp. The benefit of this study is to provide information about the successful root induction of orchid plantlets Dendrobium sp. In vitro culture and creating formulations using IBA hormones and organic plantain ingredients in in vitro culture media optimally. This research has been carried out at the YAHDI Plant Tissue Culture Laboratory. Rooting orchids Dendrobium sp. In vitro using MS basic media which was added with IBA (Indole 3 Butyric Acid) 0 ppm, 2 ppm, 4 ppm, and 6 ppm, and added with plantain pulp with levels of 0 g/l, 100 g/l. and 200 g/l. This study was a factorial experiment with 2 factors compiled based on a 4 x 3 Complete Random Design (RAL) with 12 treatment combinations. The data obtained was analyzed for variance analysis (ANOVA). If there are results that have a real effect, it is followed by the DMRT (Duncan Multiple Range Test) test at the level of 5%. (1) The results of the study showed that the treatment of the variables of the number of roots, plant height, and root length was influenced by IBA. (2) The treatment of the variables of the number of buds, the number of leaves, the number of roots, the height of the plant, and the length of the roots is influenced by plantains. (3) The treatment of the variables on the number of roots, root length, and leaf width were influenced by the interaction of IBA and banana pulp.